Gambaran Pemakaian Styrofoam Untuk Kemasan Makanan Pada Pedagang Warung Makan Dan Gerai Sekitar Anjungan Pantai Manakarra Tahun 2025 - Nuraeni, Fajar; Ahmad, Haeranah; Erwin Ashari, Agus; Adiningsih, Ridhayani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2026)
Indonesia has a high level of styrofoam usage, reaching approximately 10.95 million pieces of waste per year, including 11.9 tons from the non-household sector. The use of styrofoam packaging is becoming increasingly widespread among food vendors; however, it has never been studied in the Anjungan Pantai Manakarra area. This study aims to determine the use of styrofoam as food packaging by vendors and buyers’ preferences regarding its use around Anjungan Pantai Manakarra. The method used is quantitative descriptive, with samples consisting of 17 stalls that use styrofoam and 289 buyers.. The results show that the type of food most frequently packaged with styrofoam is fried rice (9.1%), while chicken porridge (23%) dominates among hot foods. A total of 41.2% of vendors use styrofoam because it is easy to obtain. Consumers prefer paper-based packaging (44%).In conclusion, the use of styrofoam as food packaging remains high without restrictions on the type of food, while consumers tend to choose more environmentally friendly packaging. Education and outreach are needed for vendors about the health and environmental hazards of styrofoam and the importance of using safer and more sustainable alternative packaging.